Redesigning The Layout of Finished Goods Warehouse Facilities Using The ARC Method At PT. XYZ - Handy Febri Satoto; Satria Ardiansyah Saputra (Telkom University, 2025)
PT XYZ is a company engaged in the manufacture of semi-finished wood products. Based on field observations, where products come in varying sizes and shapes, it is important to consider ergonomic aspects in layout design. Inefficiencies in the current warehouse layout were found, resulting in long material handling times and operational disruptions. The purpose of this study was to improve the layout of the finished goods warehouse area and facilities by redesigning the facility layout at PT XYZ to optimize the finished goods warehouse layout. This study used the Activity Relationship Chart (ARC) method and volume handling analysis. A redesign was proposed to improve space management and material flow. Data were collected through observation, interviews, data analysis, and discussion. The proposed layout minimizes material movement distance and improves accessibility and ergonomics. As a result, the original facility produced 26,480 units, while the proposed facility produced 15,772 units. There was a decrease in handling volume of 10,708 units, or 40.43%, after the layout change.